Assessing university student collaboration in new ways. Issue 4 (19th May 2021) - Ellis, Robert; Han, Feifei
Abstract: This study argues for the importance of using the different evidence to assess and evaluate a key graduate skill – collaboration. To do so, it investigates the experience of 356 first-year students in a blended course design and measures their collaborative patterns. Combining research methodologies from student approaches to learning and social network analysis, the results reveal evidence of different collaborative patterns across the population sample. The investigation uncovers contrasting groupings of students with deep and surface approaches to inquiry and to online learning technologies, positive and negative conceptions of the learning environment, and relatively higher or lower academic outcomes. These are discovered to logically relate to different collaborative patterns. The most effective collaboration strategies involve collaborating only as much as tasks needed, in smaller groups, and being reciprocal by accepting and inviting peers to work together. Effective collaboration strategies also include students positioning themselves to gather information easily in their collaboration networks and to develop closely knit collaborative groups. The results offer an evidence-base to identify different experiences of student learning and collaboration to improve program design and the attribute of collaboration, and to improve the concepts underpinning policy development for quality improvement of university graduates.